Hemophilia a patients with inhibitors: Mechanistic insights and novel therapeutic implications - Luo, Liping; Zheng, Qiaoyun; Chen, Zhenyu; Huang, Meijuan; Fu, Lin; Hu, Jianda; Shi, Qizhen; Chen, Yingyu (Frontiers in Immunology, 2022)
The development of coagulation factor VIII (FVIII) inhibitory antibodies is a serious complication in hemophilia A (HA) patients after FVIII replacement therapy. Inhibitors render regular prophylaxis ineffective and increase the risk of morbidity and mortality. Immune tolerance induction (ITI) regimens have become the only clinically proven therapy for eradicating these inhibitors. However, this is a lengthy and costly strategy. For HA patients with high titer inhibitors, bypassing or new hemostatic agents must be used in clinical prophylaxis due to the ineffective ITI regimens. Since multiple genetic and environmental factors are involved in the pathogenesis of inhibitor generation, understanding the mechanisms by which inhibitors develop could help identify critical targets that can be exploited to prevent or eradicate inhibitors. In this review, we provide a comprehensive overview of the recent advances related to mechanistic insights into anti-FVIII antibody development and discuss novel therapeutic approaches for HA patients with inhibitors.